CONTINUOUS HORIZONTAL CASTING INTO JET CRYSTALLIZER OF INGOTS WITH DIAMETER 70 MM OF SILUMIN AK 12 - V. Ju. Stetsenko; A. I. Rivkin; A. P. Gutev; A. M. Pevnev; R. V. Konovalov; Suk-Bong Kang (Литьë и металлургия, 2009)
It is shown that continuous horizontal casting of alloy AK12 in jet crystallizer allows to obtain ingots of 70 mm in diameter with superfine microstructure without application of modifying fluxes and addition alloys